Analisis Kemampuan Siswa SMP dalam Menerjemahkan Soal Cerita SPLDV dan Penyelesaiannya - Teguh Wibowo; Erni Puji Astuti; Anugrah Dwi Cahyani (Student Research Journal, 2023)
This study aims to determine the ability of junior high school students in translating SPLDV word problems into mathematical models and their solutions. Especially in the matter of two-variable linear equation systems (SPLDV). This type of research is qualitative. The approach used is the phenomenological approach. Data collection using test techniques, interviews, field notes, and documentation. The research subjects took 2 students with high category classification from class VIII B of SMP Negeri 2 Puring which originated from the determination of high, medium and low group boundaries. The group limit is high if the Odd PAS value is > (x ̅ + SD), the group limit is medium if (x ̅ - SD) < Odd PAS value < (x ̅ + SD), while the group limit is low if the Odd PAS value < (x ̅ + SD). Data analysis techniques include data reduction, data presentation, and conclusions. Checking the validity of the data uses credibility and confirmability tests. The results of this study indicate that the subject has a high ability to translate because he is able to understand the problem (write down what is known and asked), is able to solve problems (make examples and mathematical models), is able to take steps to solve problems. But did not evaluate or check again. Students who have high translation skills experience a few mistakes, namely not carrying out the evaluation step or checking again.